Analysis of indifference: a study based on jesuit letters in 16th and 17th century - Barros, Mariana Leal de; Massimi, Marina (Paidéia (Ribeirão Preto), 2005)
This study comprehend the conceit of indifference, what is analyzed in the Litterae Indipetae, letters that jesuits have asked to the Jesus Company to go to the Mission, in the centuries XVI and XVII. The document show the particularity from each t account specially because of the explanation about the desire of to serve overseas, what configure the wealth on the point of view by the psychological, religious and social. The content analysis was based on the the documents context, with an emphasis on the formal letters structure undertanding, the rhetoric of this period, and the philosophical base of the Company and the rules that characterize her. The objective is based on the study of the letters, which the jesuits set themselves indifferent about the place that, they could to serve. So, it was observed that the indifference is a concept own of the jesuit's spirituality and it´s important to understand the psicology in this epoch, because still is associate with the ideas of courage, deliberation about the desire and middle- term.